ANALYSIS OF THE ROLE OF STAKEHOLDER IN THE DEVELOPMENT OF SUSTAINABLE FOREST WAQF (STUDY CASE ON BOGOR WAQF FOREST FOUNDATION) - Ahmad Zaeni; Bayu Taufik Possumah; Indra (Department Islamic Economics, 2022)
Purpose– This study analyzes the role of stakeholders concerning waqf forests. This study aims to determine the stakeholders who influence the forest waqf development program and to measure each stakeholder's influence and interest level in the forest waqf development program.Design/methodology/approach– This research uses a case study approach on Bogor Waqf Forest Foundation, with qualitative research methods. The research collected data through field observations and in-depth interviews with the key informants (Key Persons).Findings–. The results showed that there were 16 stakeholders classified into five groups: the central government, local government, private sector, community, and academy. Based on the finding, the influence and interest analysis show themapping of stakeholder roles into four quadrants: subject, key player, context setter, and crowd.Research limitations/Implications– This study interprets the results of a quantitative analysis of the role of stakeholders in Bogor Waqf Forest. Therefore the results can be considered while running decisions making process especially for policymakers. This study complements research related to forest waqf stakeholders, which is still limited and can be the beginning of other related studies, for example, by using different research methods or carried out in other places that are also developing forest waqf.Originality/value– This study adds to the library of similar research that analyzes stakeholders, which has never been carried out with waqf forests as a case study.Keywords- Stakeholder, waqf forest, waqf development